2018
DOI: 10.18632/oncotarget.24699
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hospital volume and short-term outcomes: a nationwide population-based study including 75,280 rectal cancer surgical procedures

Abstract: There is growing interest on the potential relationship between hospital volume (HV) and outcomes as it might justify the centralization of care for rectal cancer surgery.From the National Italian Hospital Discharge Dataset, data on 75,280 rectal cancer patients who underwent elective major surgery between 2002 and 2014 were retrieved and analyzed. HV was grouped into tertiles: low-volume performed 1-12, while high-volume hospitals performed 33+ procedures/year. The impact of HV on in-hospital mortality, abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Some 18·4 per cent of all operations were emergency procedures, an unexpectedly high proportion. These cases will increase the expertise of surgeons in individual hospitals, but could have biased the mortality analysis as they were not equally distributed across the quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…Some 18·4 per cent of all operations were emergency procedures, an unexpectedly high proportion. These cases will increase the expertise of surgeons in individual hospitals, but could have biased the mortality analysis as they were not equally distributed across the quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be the result of a more accurate patients selection and a better ability to rescue patients after surgery, since the mortality of patients in high-volume hospital was found to be almost half compared to low-volume centers (0.9% vs. 1.6%, p < 0.001). To confirm the hypothesis of better patients selection, in a previous study using the same cohort of patients, we showed that patients admitted to low-volume hospitals were more likely to be older (p < 0.001), have a worse Charlson Comorbidity Index (p < 0.001), have a higher rate of stoma creation (p < 0.001), and being treated with an open approach (p < 0.001) [11]. Based on these findings it is important to implement a program of centralization of care and a system of evaluation of patient care nationwide, aiming to improve patient selection, perioperative management and quality standards.…”
Section: Discussionmentioning
confidence: 56%
“…Hospital volume has been widely used to characterize the quality of care, mostly defined in terms of in hospital mortality, length of stay and readmission [11]. FTR has been recently introduced as a metric of quality of care and researchers correlated it with hospital volume and type (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average LOS varies according to the type of procedure considered. Pucciarelli et al [9] analysed 75280 patients submitted to cancer colorectal procedures and the median LOS was 13 days [9], while Nassour et al [10] reported a median LOS of 11.5 days for robotic and 11.8 days for laparoscopic pancreaticoduodenectomy [10]. Our higher ALOS when compared to the literature is probably a consequence of the complexity of our co-managed patients: oncological surgical patients with high risk procedures and their possible complications, prolonged recovery and multiple medical comorbidities.…”
Section: Discussionmentioning
confidence: 78%